Singapore-Malaysia relations under Abdullah Badawi - Saw, Swee-Hock, 1931- (Gale virtual reference library, 2006)
Documents the series of important events that have contributed to the warmer relations presently enjoyed by Singapore and Malaysia under Abdullah Badawi.